Renoprotective Effect of the Recombinant Anti-IL-6R Fusion Proteins by Inhibiting JAK2/STAT3 Signaling Pathway in Diabetic Nephropathy - Zhang, Nanwen; Zheng, Qingmei; Wang, Yaduan; Lin, Juan; Wang, He; Liu, Rui; Yan, Mengru; Chen, Xiaofeng; Yang, Juhua; Chen, Xiaole (Frontiers in Pharmacology, 2021)
Diabetic nephropathy (DN) ,the main reason for end stage renal disease (ESRD), is a common microvascular complication in patients with type 1 and type 2 diabetes. The interleukin-6 (IL-6), acting as a pleiotropic cytokine, plays key roles in main autoimmune disorders. The recombinant anti-IL-6R fusion proteins (VHH-0031) constructed and obtained in our lab is a dual target-directed single domain-based fusion protein against the interleukin-6 receptor. This study aimed to explore renoprotective effect of VHH-0031 in diabetic nephropathy. VHH-0031 treatment alleviated renal inflammation, morphologic injury and renal insufficiency in both GK rats and STZ-induced SD rats. These renoprotective effects of VHH-0031 were associated with alleviating inflammation and suppression of the JAK2/STAT3 signaling pathway. The mesangial cells treated with VHH-0031 exhibited anti-proliferation, anti-inflammation and inactivation of JAK2/STAT3 pathway under high glucose condition. In conclusion, this study demonstrates that VHH-0031 exhibited a potent protective effect in kidney of diabetic rats and its mechanism may be concerned with the inhibition of the IL-6R/JAK2/STAT3 pathway of glomerular mesangial cells.